Pengaruh Media Ceramah, Kipas dan Poster Terhadap Peningkatan Pengetahuan Junk Food pada Remaja Awal - Luthfiya, Lulu'; Khoiriyah, Mufidatul; Nabawiyah, Hafidhotun; Pibriyanti, Kartika; Pinasti, Ladya Mayu (UI Scholars Hub, 2025)
Background. Consuming excess junk food lead to degenerative diseases and cause various nutritional problems. This is due to the lack of information regarding the dangers of junk food in teenagers from education media. Fan media and posters as a media intermediari for delivering information related to the dangers of junk food in adolescents. Aim. This study conducted to determine the effect of educational media of lecturer fan and poster) on knowledge of junk food in adolescents. Method. The study was conducted by quasi-experimental method with a pre-post test group design. Sample was 174 respondents that divided into 3 groups there were fan media (n=58), posters (n=58) and lectures (n=58). The sample calculation formula was lamsehow and the technique sampling was purposive sampling method. Each group was held 1 meeting. Knowledge data was obtained by filling out pre and post test questionnaire after intervention. All three groups were tested using the Wilcoxon test, Kruskal Wallis test, and followed by the Mann-Whitney post-hoc test. Result. The result of the pre-post test in the three groups was p-value = 0.000 and the result of the difference in knowledge between the media of fan was 6.00, posters were 11.00 and lectures were 5.50. Conclusion form this research there was an increase in knowledge on fan media and posters with a value of p = 0.000 (0.05). The best media on this research was poster.